A snapshot of woody plants composition in Byram permanent mangrove forest reserve - Wan Nur Fasihah Zarifah Binti Wan Rozali; M. Asyraf (Syiah Kuala University, 2012)
The term mangrove may refer to an ecosystem or individual plants where the distribution of woody plants usually influenced by climate, water salinity, tides, type of soil in the mangrove swamps and environmental activities including development, housing and industrial. Thus only a certain species that can survive under this extreme condition. A study had been conducted in Byram Permanent Mangrove Forest Reserve to provide baseline information on the distribution pattern of plant growth in mangrove area. The main objective of this study is to determine the composition and the distribution pattern of true-mangrove woody plant species. To assess the species composition, the forest reserve nearest to the sea, which run approximately 2.0 km, parallel to the sea, was divided into three main sections (i.e. 600 m each section with a minimum 50 m wide border between the sections). Species enumeration was conducted in 11 plots, where each plot size is 10m x 10m. In general these plots were established in random stratified manner, from the sea towards the terrestrial part of the mangrove forest. In total, we recorded 290 of individual woody plants. The most abundant species in term of occurrences within all zones and forest section is Bruguiera parvifolia.